Film Cooling from Two Staggered Rows of Compound Angle Holes at High Blowing Ratios - Phillip M. Ligrani; Joon Sik Lee (International Journal of Rotating Machinery)
Experimental results are presented which describe the development and structure of flow downstream of two staggered rows of film-cooling holes with compound angle orientations at high blowing ratios. These film cooling configurations are important because they are frequently employed on the first stage of rotating blades of operating gas turbine engines. With this configuration, holes are spaced 3d apart in the spanwise direction, with inclination angles of 24 degrees, and angles of orientation of 50.5 degrees. Blowing ratios range from 0.5 to 4.0 and the ratio of injectant to freestream density is near 1.0. Results show that spanwise averaged adiabatic effectiveness, spanwise-averaged iso-energetic Stanton number ratios, surveys of streamwise mean velocity, and surveys of injectant distributions change by important amounts as the blowing ratio increases. This is due to injectant lift-off from the test surface just downstream of the holes which becomes more pronounced as blowing ratio increases.